Gross morphometry of human placenta in eclampsia - Sultana, S; Hossain, GA; Rahman, H; Mannan, S; Zannat, S (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):10-4 The abstract of this article is available on the PubMed website